2023
DOI: 10.1021/acs.iecr.3c03173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Number of Rotors in Rotating Packed Beds on Separation Performance in Distillation

Tobias Pyka,
Vincent Backhaus,
Christoph Held
et al.

Abstract: Different configurations of a rotating packed bed (RPB) were used in a distillation study to comprehend the impact of the number of rotors on the separation performance of ethanol/1-propanol distillation at total reflux and atmospheric pressure. The separation performance of a single-rotor RPB (1R-RPB) was compared with that of a two-rotor RPB (2R-RPB). To achieve a uniform liquid distribution in the lower rotor of the 2R-RPB, a liquid collector and a rotating baffle distributor (RBD) were installed. The rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Contrary to liquid injection with SPFJ nozzles, the liquid is specifically accelerated at each new rotor stage using RBDs, which guarantee defined boundary conditions at each new rotor stage in terms of liquid distribution (Figure ). Therefore, an RBD does not necessarily require such central liquid inlet as in single-rotor RPBs, which was recently demonstrated in a multirotor RPB distillation study where the RBD was applied in the lower rotor and upper rotor . The angle of the droplet breakup (α) can be determined by connecting the outer edge of the baffle with the entry of liquid toward the packing (see Figure a).…”
Section: Methodsmentioning
confidence: 98%
“…Contrary to liquid injection with SPFJ nozzles, the liquid is specifically accelerated at each new rotor stage using RBDs, which guarantee defined boundary conditions at each new rotor stage in terms of liquid distribution (Figure ). Therefore, an RBD does not necessarily require such central liquid inlet as in single-rotor RPBs, which was recently demonstrated in a multirotor RPB distillation study where the RBD was applied in the lower rotor and upper rotor . The angle of the droplet breakup (α) can be determined by connecting the outer edge of the baffle with the entry of liquid toward the packing (see Figure a).…”
Section: Methodsmentioning
confidence: 98%
“…Total reflux distillation experiments showed that the distributor led to a higher separation efficiency, compared to the conventional nozzle liquid distributor. Pyka et al 12 compared the pressure drop and the separation performance of a single-rotor RPB with those of a two-rotor RPB at the same operating conditions. Results showed that the pressure drop as well as the separation performance in the two-rotor RPB could ideally be twice as high as those of the single-rotor RPB.…”
Section: Introductionmentioning
confidence: 99%